Palladium-catalyzed Mizoroki–Heck-type reactions of [Ph2SRfn][OTf] with alkenes at room temperature. Issue 80 (2nd September 2016) - Wang, Shi-Meng; Song, Hai-Xia; Wang, Xiao-Yan; Liu, Nan; Qin, Hua-Li; Zhang, Cheng-Pan
Abstract : The first Pd-catalyzed Mizoroki–Heck-type cross-coupling of phenylsulfonium salts with alkenes was disclosed at room temperature. Abstract : The first Pd-catalyzed Mizoroki–Heck-type reaction of [Ph2 SRfn ][OTf] with alkenes is described. The reaction of [Ph2 SRfn ][OTf] (Rfn = CF3, CH2 CF3 ) with alkenes in the presence of 10 mol% Pd[P( t -Bu)3 ]2 and TsOH at room temperature provided the corresponding phenylation products in good to high yields. The bases that benefit the traditional Mizoroki–Heck reactions severely inhibited the transformation with [Ph2 SRfn ][OTf], whereas acids significantly improved the reaction. This protocol supplies a new class of cross-coupling partners for Mizoroki–Heck-type reactions and gains important insights into the reactivity of phenylsulfonium salts either with or without fluorine-containing alkyl groups as the promising phenylation reagents in organic synthesis.